Outcomes of Transmastoid Surgery for Superior Semicircular Canal Dehiscence Syndrome. Issue 7 (August 2016) - Powell, Harry R. F.; Khalil, Sherif S.; Saeed, Shakeel R.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To present the management strategy and outcomes for our series of superior semicircular canal dehiscence syndrome (SSCDS) patients. Study Design: Retrospective cross-sectional study. Setting: Tertiary referral center. Patients: Thirty-seven consecutive patients referred from June 2011 to January 2015. Diagnosis of SSCDS based on presence of classical symptoms, computerized tomography, and concordant reduction in cervical vestibular evoked myogenic potentials. Interventions: Transmastoid resurfacing or plugging. Main Outcome Measures: Pre- and postoperative pure tone audiometry. Nine item questionnaire grading pre- and postoperative symptom severity. Results of a short semi-structured telephone survey. Results: Twenty surgical patients: 13 women and 7 men. Mean age 52 years 6 months. Eighteen patients underwent transmastoid resurfacing and two underwent transmastoid plugging. Three of those who initially had resurfacing but had ongoing SSCD symptoms, subsequently had transmastoid plugging with complete resolution of third window symptoms. From the questionnaire there was improvement in mean scores for 8 of 9 of the SSCD symptoms, with statistically significant improvement in 6 of 9. Conclusions: Management strategies and surgical techniques continue to evolve for SSCDS. We currently offer transmastoid resurfacing having informed patients of a 25% possibility of incomplete symptom resolution, and explain that plugging can be performed as a "second stage, " if necessary. However, as we accrue more experience and there is more evidence from the literature we are considering whether to offer transmastoid plugging as our primary surgical procedure. In our experience, patients with multiple vestibular pathologies or atypical vestibular symptoms are the ones for whom SSCD surgery has not been curative, although they do report improvement in their SSCD symptoms.